China's global value chain linkage and logistics performances in emerging ASEAN economies. Issue 2 (17th July 2022) - Taguchi, Hiroyuki; Zhao, Jun
Abstract: This paper aims to evaluate the extent of China's forward linkage of global value chains (GVCs) with emerging market economies of the Association of Southeast Asian Nations (ASEAN) compared to those with the United States and Japan, and also to examine the nexus of China's forward GVC linkage with logistics performances in emerging ASEAN economies as China's trade partners. This study uses the UNCTAD‐Eora Database and applies a structural gravity trade model for empirical analysis. The statistical observations identified the major position of China's GVC, which has transformed from a backward linkage to a forward linkage since the mid‐2000s. The empirical estimation verified that there is less linkage in China's forward GVC with emerging ASEAN economies than with the United States and Japan, and demonstrated that the lack of logistics performances in emerging ASEAN economies has been a significant factor in explaining the less linkage in China's forward GVC with them.